2016
DOI: 10.1109/jlt.2016.2577341
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Compact Polarization Splitter by Using Identical Coupled Silicon Nanowires

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Polarization beam splitter (PBS) is widely used to mitigate the polarization randomness problem in photonics systems by controlling the polarization state, thus, ensuring proper functioning [16][17][18][19][20]. PBS has been extensively used in sensor applications, such as polarization navigation sensor [21], photoacoustic remote sensing microscopy [22], distributed vibration sensor [23], magnetic field sensor [24], and fiber-optic gyroscope [25].…”
Section: Introductionmentioning
confidence: 99%
“…Polarization beam splitter (PBS) is widely used to mitigate the polarization randomness problem in photonics systems by controlling the polarization state, thus, ensuring proper functioning [16][17][18][19][20]. PBS has been extensively used in sensor applications, such as polarization navigation sensor [21], photoacoustic remote sensing microscopy [22], distributed vibration sensor [23], magnetic field sensor [24], and fiber-optic gyroscope [25].…”
Section: Introductionmentioning
confidence: 99%
“…Directional couplers perform optical power exchange between usually two closely lying waveguides via the access of this evanescent effect, sensitive to the wavelength and polarization because of the dispersive nature of such mode interference couplers. They found many applications in, e.g., wavelength multiplexers/demultiplexers and polarization splitters [1][2][3]. On the other hand, the study of waveguide couplers working with broad spectral bandwidth has been in demand for important applications in especially optical communication and networking systems (for such as power or mode division, exchange, or switch [4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
“…LiNbO 3 , renowned as "the silicon of photonics", has been long a popular (and perhaps the most important) material for building various integrated optical circuits/devices (reviews of the recent development in LiNbO 3 photonics can be found in [15][16][17]) because of its versatility derived from its excellent electro-optic (EO), acousto-optic, nonlinear-optic (NLO), and piezoelectric properties with wide optical transparent range (~0.4-5 μm) [18]. It will thus be interesting and desirable to develop a broadband polarization splitter in LiNbO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Mode-division multiplexing (MDM) has been shown to be more suitable for photonic integrated circuits (PIC) [3,4]. However, power transfer between the two orthogonal modes may occur in MDM systems, which is a major problem in communications and sensing systems [5]. Accordingly, there is a serious need for polarization handling devices, which include polarization beam splitters, polarization rotators, and polarizers.…”
Section: Introductionmentioning
confidence: 99%